Relationship of phonological awareness and word recognition to comprehension of texts among selected pupils in Ibadan, Oyo State (2018)
This descriptive survey was conducted in Ibadan North Local Government Area of Oyo State. A total of l77 pupils were involved in the study. A multi-stage sampling technique was employed and a self-designed Pupils' Reading inventory war administered to elicit data. Four research questions and two hypotheses were generated and tested. Mean, frequency computation, and KruskaI-Wallis test were the statistics used to analyze the data. The results of the analysis showed that there is a statistically significant difference in the means of the variables at 5% level of significance, thus, leading to the rejection of our H01. Also, the relationship that holds among the independent variables shows positive correlation though there P-value varies. It is therefore argued that reading comprehension and by large comprehension in human communication has its foundation in explicit knowledge of language phonological structure as decoding skills are paramount to effective comprehension. The study revealed that there is dependency relation between phonological awareness. word recognition and reading comprehension to varying levels. On this basis, it was recommended that teachers should therefore endeavour to reinforce pupils' knowledge of the decoding skills of reading to enhance pupils reading performance.